Comprehensive profile and natural history of pediatric patients with spinal muscular atrophy: A large retrospective study from China - Hu, Chaoping; Li, Xihua; Shi, Yiyun; Zhu, Xiaomei; Zhao, Lei; Li, Wenhui; Zhou, Shuizhen; Wang, Yi (Frontiers in Neurology, 2022)
Background There is a large population of people with spinal muscular atrophy (SMA) in China, and new disease-modifying therapies have become available recently. However, comprehensive data on the management and profile of treatment-naive SMA patients in China are still lacking. Methods As a retrospective study, a large cohort of treatment-naive patients with clinical and genetic diagnoses of 5q SMA were enrolled, ranging from neonatal to 18 years old, from the Neurology Department of Children’s Hospital of Fudan University between January 2013 and December 2020. The data regarding their clinical presentations, genetic defects, motor function assessment results, and follow ups were reviewed. Results We enrolled 392 SMA patients (male: female=189: 203): 1a=46, 1b=44, 1c=31, 2a=119, 2b=56, 3a=52, 3b=14, from 27 of the 34 administrative districts in China, and 389 patients harbored homozygous deletion of exon 7 in the SMN1 gene (99.2%). The median age of onset was 0.08(range: 0-0.30), 0.25(0.06-0.60), 0.42(0.08-1.50), 0.67(0.07-5.08), 1.0(0.40-1.83), 1.5(1.00-3.00) and 4.04(1.80-12.00) years old for SMA 1a, 1b, 1c, 2a, 2b, 3a, and 3b patients, while the median age of first assessment was 0.25(0.08-2.60), 0.42(0.17-1.90), 0.80(0.17-4.5), 2.50(0.5-15.83), 2.92(1.08-13.42), 4.25(1.58-17.33), and 7.34(3.67-14.00) years old, respectively. Patients were followed up with for up to 15.8 years. The median event-free survival time was 7 months, 15 months, and indeterminate in SMA 1a, 1b and 1c patients (p<0.0001), with a better survival situation for higher SMN2 copies (p=0.0171). The median age of sitting loss was 5.75 years and 13.5 years in SMA 2a and 2b (p=0.0214) and that of ambulation loss was 9.0 years and undefined in SMA 3a and 3b (p=0.0072). Cox regression analysis showed that higher SMN2 copies indicated better remaining ambulation in SMA 3. The median time to develop orthopedic deformities was 4.5, 5.2, and 10.1 years in SMAs 1c, 2, and 3, respectively (p<0.0001), with a possible trend of better preservation of joint function for patients under regular rehabilitation (p=0.8668). Conclusion Our study elucidated insight into the comprehensive management and profile of different types of SMA patients in China, providing a clinical basis for assessing the efficacy of new therapies.